How to get away with colour: Colour-blindness and the myth of a postracial America in American television series - Emiel Martens; Débora Póvoa (Alphaville: Journal of Film and Screen Media, 2017)
The popular American television series How to Get Away with Murder (2014) seems to challenge the long history of stereotypical roles assigned to racial minorities in American media by choosing a multiracial cast to impersonate characters that, while having different racial backgrounds, share a similar socio-economic status and have multidimensional personalities that distance them from the common stereotypes. However, although it has been praised for its portrayal of racial diversity, the series operates within a problematic logic of racial colour-blindness, disconnecting the main characters from any sign of racial specificity and creating a fictional world in which racism is no longer part of American society. This case study aims to demonstrate to which extent the “colour-blind approach” of the TV show reinforces the postracial illusion in the United States, i.e. the idea that the country has overcome its past of racial segregation and now offers the same opportunities for everyone, regardless of colour and race. Through a narrative analysis of the first season of the series, this chapter will argue that the depiction of race in How to Get Away with Murder is highly ambivalent. On the one hand, the show does not completely ignore race by inserting topics such as racism in the plot, giving these issues at least some visibility. On the other hand, its more general panorama reveals an intent to deracialise its main characters in a colour-blind manner. This is problematic since it overshadows racial issues that still have a big impact on the lives of racial minorities.